Hubungan Komunikasi Organisasi dengan Konflik Kerja Pada Perusahaan PT. Kimia Farma, Tbk. Cabang Makassar - Aswar Aswar; Puspita Noer Patriani (Jurnal Komunikasi Global, 2018)
This study aims to determine the relationship between organizational communication and workplace conflict in PT. Kimia Farma, Tbk. Makassar Branch. The paradigm in research is positivism to see the relationship between the two variables in this study. The measuring instrument in this study is the scale of organizational communication and work conflict using the Likert scale. The number of samples was 54 employees who were determined using the Slovin formula and selected using the simple random sampling method from 118 people in total. Data were collected through a survey. It was used Pearson Product Moment test to analyze data with the help of SPSS 22.0. The results of the study show that there is a negative and significant relationship between organizational communication and workplace conflict at PT. Kimia Farma Tbk. Makassar Branch. The correlation coefficient between organizational communication and work conflict is -0.781 or 78.1% with a significance value of p less than 0.000. It can be concluded that if all people in the organization have good organizational communication, the possibility for the workplace conflict will decrease, and vice versa.